Biotechnological potential of cellulolytic nitrogen-fixing Klebsiella sp. C-3 isolated from paddy soil. (February 2021) - Harindintwali, Jean Damascene; Zhou, Jianli; Habimana, Ildephonse; Dong, Xuetian; Sun, Chixiang; Nwamba, Marknoah Chinenye; Yang, Wenhua; Yu, Xiaobin
Abstract: In the present study, a new thermo-adaptive cellulolytic nitrogen-fixing bacterial strain designated as Klebsiella sp. C-3, which could degrade cellulose and hemicellulose in rice straw (RS) without an added nitrogen source, was isolated from paddy soil. The highest activities of enzymes (FPase, 0.92 IU/mL, and Xylanase, 17.1 IU/mL) produced by Klebsiella sp. C-3 were recorded at 37 °C. In RS hydrolysate, the % of the total nitrogen content increased from 0.65% to 3.7% after 7-day fermentation with Klebsiella sp. C-3. The main reducing sugar products of RS hydrolysate were glucose, xylose, and cellobiose. Unexpectedly, Klebsiella sp. C-3 had much lower water loss (30%) than the control group (61.85%) and other bacterial isolates at 45 °C after a 7-day incubation period. Hence, Klebsiella sp. C-3 could provide a feasible pathway to manage lignocellulosic biomass in soil and improve water retention in thermophilic biological processes and arid soils. Graphical abstract: Unlabelled Image Highlights: A cellulolytic nitrogen-fixing Klebsiella sp. C-3 was isolated from paddy soil. C-3 hydrolyzed rice straw components without an added nitrogen source. C-3 showed a high water retention capacity under thermophilic conditions.